RESERVATION SYSTEM DESIGN OF GOODS IN PT. POWER CIPTA LESTARI - Ferry Raymond; Ir. Don Elsyafitra Ir. Don Elsyafitra (Jurnal Sistem Informasi, 1999)
PT. Daya Cipta Lestari is one company that is engaged in ordering furniture items, the company is domiciled in Jakarta. Since the inception of this company, its management system is done manually (system book) after the progress and technological development was so rapid, especially in the field of computers these companies take advantage of the development of computer systems by change of all books into a computerized system where the system is intended for data processing quickly and appropriately so useful to the users and also to avoid the mistakes that can be done on the system book. With the computerization and qualified human resources to achieve the desired results in accordance with.